Memory and storytelling. The path from parental memories to a nation-building myth for children - Korábková, Kateřina (My University, 2024)
This paper focuses on how October 28—Czechoslovak Independence Day—is presented in children’s sections and supplements in newspapers of inter-war Czechoslovakia. Examination of various types of texts intended for children reveals several basic interpretations of this important day. The paper aims to describe the characteristics taken on by the formation of a nation-building myth for children, which transforms the collective memory of parents into a historical memory serving to create and strengthen national identity.
Paměť a vyprávění. Cesta od paměti rodičů k národotvornému mýtu pro děti
Keywords: October the 28th 1818; interwar Czechoslovakia; children's columns and newspaper supplements; national myth; collective memory; historical memory; identity; 28. říjen 1818; meziválečné Československo; dětské rubriky a přílohy novin; národotvorný mýtus; kolektivní paměť; historická paměť; identita